Do Disruptive Life Events Affect How Analysts Assess Risk? Evidence from Deadly Hurricanes - Bourveau, Thomas; Law, Kelvin K. F. (The Accounting Review, 2021)
ABSTRACT This study examines whether disruptive life events affect how analysts assess risk. We exploit the staggered arrival of hurricanes between 1996 and 2009 at analysts' office locations across the United States as a plausibly exogenous shock in the analysts' experience of disruptive life events. We show in a difference-in-differences setting that relative to non-affected analysts, analysts in states affected by hurricanes issue less optimistic forecasts for non-affected firms after hurricanes. The temporary effects are strongest for affected analysts who had never before experienced a hurricane in their office location. The evidence suggests that analysts use the availability heuristic to assess risk. We observe the same effects in recent years, as our analysis based on Superstorm Sandy in 2012 yields similar results. Overall, our evidence indicates that disruptive life events affect analysts' judgments. JEL Classifications: D81; D83; G02; G24; G29.